Molecular evidence of Brucella abortus circulating in cattle, goats, and humans in Central Equatoria State, South Sudan - Emmanuel P. Lita; Ernatus M. Mkupasi; Erneo B. Ochi; Gerald Misinzo; Henriette van Heerden; Robab Katani; Jacques Godfroid; Coletha Mathew (Scientific Reports)
Abstract Brucellosis is a neglected zoonotic disease in most developing countries, including South Sudan. Precise identification of Brucella species is crucial for addressing public health and epidemiological concerns associated with brucellosis. The study aimed to identify Brucella species using real-time polymerase chain reaction (qPCR) from seropositive samples that were acquired from an earlier investigation. A total of 143 genomic DNA samples were extracted from brucellosis Rose Bengal plate test (RBPT) seropositive samples from humans (n = 7), cattle (n = 103) and goats (n = 33). The samples were collected from Terekeka and Juba counties, Central Equatoria State (CES), South Sudan. The qPCR targeting the Brucella-specific IS711 insertion gene at the genus level was performed. Samples with a cycle threshold (Ct) of ≤ 35 were considered positive and subjected to further Brucella speciation assays. Out of 143 DNA samples tested for genus-specific Brucella, 15 (10.5%) were positive including 4 (2.8%) from humans, 10 (6.9%) from cattle, and 1 (0.7%) from goats. Brucella abortus was identified in 5 (33.3%) of the positive samples at the genus level. The overall individual species infection rates with B. abortus were 6.6% (1/15) in humans, 20% (3/15) in cattle, and 6.6% (1/15) in goats. There was no B. melitensis detected in this study. This study identified B. abortus in cattle, goats and humans in CES, South Sudan. The findings suggest that cattle are probably the primary reservoirs for transmission of B. abortus, with infections occurring in goats and humans primarily resulting from cattle spillover.